YOUTH IN POSTMODERN SOCIETY CHANGES IN THE WORLD - Nurbek Aminov (Galaxy International Interdisciplinary Research Journal, 2022)
In this article the features of changes in the worldview of the youth in postmodern society are explained. The impact of modern civilization on the mentality of the youth, in turn, is analyzed as a result of major changes of social consciousness in postmodern society. The peculiarities of postmodern society are studied on a scientific basis.